Interpretations of Melodic Framework and Instrumental Idiom in a Metrically Fluid Piece of Central Javanese Music Performed on a Busking Zither - Rohan Iyer (Analytical Approaches to World Music)
This article examines a recorded performance of a piece of music adapted from the Central Javanese court repertoire of pathetan to a large Javanese zither (siter barung). This solo instrumental rendition of a pathetan on a siter barung is very unusual, as the family of zithers do not usually partake in this genre of pieces, even within the realm of court-style gamelan music. A busker (ngamen), who belongs to a troupe of musicians that comprise a siteran ensemble, plays the zither. The pathetan is a metrically fluid genre of Javanese music, which holds important mode defining and mood setting functions across different performance contexts. Ngamen siteran troupes are made up of itinerant street musicians who primarily perform light, vocal genres of music. Transcription and analysis of the piece “Pathetan Sléndro Manyurå Jugag” reveals that the siter barung largely adheres to the standard court-style melodic framework. By comparing this performance to a court-style rendition of the same piece on a large Javanese metallophone (gendèr barung), aspects of performative interpretation particular to the siter barung instrumental idiom and to rural/village styles of Central Javanese performance are highlighted. This study hopes to provide a model upon which pathetan can be (re)-introduced into ngamen and court-style siteran contexts.